Parental Support in Preventing Online Sexual Violence in Children with Intellectual Disabilities - Kelrey, Fathimah; Latuperissa, Glorya R.; Pangandaheng, Tommy (Indonesian Journal of Global Health Research, 2024)
Online-based sexual violence on the internet through the use of social media is increasingly widespread and rapid in society and is a threat to children, especially children with special needs or intellectual disabilities due to limited intellectual functions which affect adaptive behavior, social, conceptual and practical skills in everyday life. So they need parental support to prevent this from happening. Objective : The purpose of this study is to analyze the relationship between parental support in preventing online sexual violence in children with intellectual disabilities. Method: This research uses a descriptive phenomenological approach which is qualitative research. The total research sample was 7 participants using purposive sampling. The research instrument is the researcher as the instrument who will interview participants in depth (in depth interview) which requires the researcher to interact directly with the data source, in other words the researcher must really know who the participants are in 4 meetings. Data was analyzed using thematic analysis. Results: The main findings are 3 themes, namely 1) Parents' knowledge about online sexual violence is not yet optimal, 2) unclear limits or rules for how long cell phones can be used to access social media or games and social media used by children with intellectual disabilities in interacting and 3) Parents do not always accompany their children to use cellphones or use social media. Conclusion: There is a need for parental support in providing optimal online sexual violence information, providing time to always accompany children using cellphones or social media and implementing consistent time limits in preventing sexual violence in children with intellectual disabilities.